METODE TASMI’ DALAM MEMBELAJARKAN TAHFIDZ AL-QUR’AN BAGI ANAK USIA DINI - Nurul Huda; Vita. Fitriatul Ulya; Faza Karimatul Akhlak (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2022)
This study was conducted to determine the learning method for memorizing the Qur'an (tahfidz al-Qur'an) for early childhood which was applied in TK IT Al-Hakim Kids Kalianda. This research is a type of qualitative research using data collection methods through interviews, observation and documentation. The next researcher describes the research findings in the form of words or descriptive narratives. The subjects of the research were the IT Kindergarten teacher Al-Hakim Kids Kalianda, and the research informants included students and parents. The results showed that the method of memorizing the Qur'an that was applied in TK IT Al-Hakim Kids Kalianda was using the Tasmi' method. Factors that support the program of memorizing the Qur'an (tahfidz al-Qur'an) are seen from the factors of age, intelligence, environment, and competent teachers who are fluent in reading the Qur'an, are always trained, and always do muroja'ah with students. While the inhibiting factors include the delay of children entering class and the absence of children so that it will hinder memorization and lag behind in memorizing. Then the memorization that has been done in kindergarten is not repeated at home with his parents. The efforts taken in achieving the success of children memorizing the Qur'an in addition to the cooperation of the kindergarten with parents also do several things, namely: memorizing the Qur'an do not rush, memorize short letters, make memorization targets, by giving praise and gifts, create a pleasant and comfortable atmosphere, choose a teacher who is competent in memorizing, know how children learn, give children limits on watching TV and gadgets for children, and guide and control children's memorization while at home